A. y = 2(x + 5)2 + 4

B. y = 2(x - 5)2 + 4

C. y = 2(x + 5)2 - 4

D. y = 2(x - 5)2 - 4

A. y = 2(x + 5)2 + 4

B. y = 2(x - 5)2 + 4

C. y = 2(x + 5)2 - 4

D. y = 2(x - 5)2 - 4

Tutors, please sign in to answer this question.

New Baltimore, MI

Case A: 2*(5 + 5)^2 + 4 = 2*(10)^2 + 4 = 2*100 + 4 = 204 does not equal -4

Case B: 2*(5 - 5)^2 + 4 = 2*(0)^2 + 4 = 2*0 + 4 = 4 does not equal -4

Case C: 2*(5 + 5)^2 - 4 = 2*(10)^2 - 4 = 2*100 - 4 = 196 does not equal -4

Case D: 2*(5 - 5)^2 - 4 = 2*(0)^2 - 4 = 2*0 - 4 = -4

The answer is D.

Amaan M.

Former High School Math and Economics Teacher

New York, NY

5.0
(56 ratings)

Elliott L.

Ph.D. Math Tutor, High School and Early College Subjects

New York, NY

4.9
(275 ratings)

Adam P.

Highly Experienced Test Prep Instructor

Brooklyn, NY

4.9
(80 ratings)

- Algebra 1 3235
- Math 7231
- Algebra 4053
- Math Help 4185
- Precalculus 1254
- Geometry 1476
- Algebra Help 888
- Word Problem 4022
- Algebra Word Problem 2037
- Algebra 2 Question 437